Variasi bahasa â€œsapaan pemirsaâ€ pada konsep siaran audio - Eva Mizkat (Jurnal Komunitas Bahasa, 2023)
The variety of languages used by speakers or a group of people will shape the variety of languages in sociolinguistic studies. This research discusses the variation of language "greeting viewers" in the case study assignment of students in Broadcast Engineering course which aims to see the variations of language used to attract listeners/viewers of audio broadcasts. Both through diction and grouping of words used in various Indonesian languages, also to analyze student creativity in exploring their linguistic potential which is influenced by social and cultural factors. This type of research is qualitative using content analysis techniques. Sources of data from the documentation of student assignments conceptualizing broadcast language on audio broadcast technique material in class IV C in the form of writing (written text) totaling 15 data. The results obtained are language variations in the casual variety of 8 data, the intimate variety of 5 data, the official (formal) variety of 2 data. However, data 7 and data 13 tend to be in the slang group which is currently trending.